Indigenous youth suicide - Cormier, Patrice (Author); Hogg, John (Chair); Storey, Patrick (Committee member); Chan, Adrienne (Committee member); University of the Fraser Valley School of Social Work and Human Services (Degree granting institution) (University of the Fraser Valley, 2020)
Indigenous youth suicide is a grave concern among Indigenous communities in Canada. While suicide rates for non-Indigenous Canadians have decreased, the suicide rate for Indigenous youth remains three to four times higher than the national average (Young et al., 2016). The need for effective interventions to prevent Indigenous youth suicide is uncontested. Despite this need, the effectiveness of interventions for Indigenous youth suicide remain mixed. The most common approaches, informed by a Western lens, have demonstrated limited success. Practical alternatives are being developed, based on Indigenous worldview and recent interventions developed by Indigenous people for Indigenous youth, families, and communities. These culturally informed, culturally safe grassroots approaches described herein, highlight cultural and community-based interventions for Indigenous communities. Through a critical review and amalgamation of current, relevant empirical and theoretical literature, this paper examines intervention approaches typically used to respond to Indigenous youth suicide intervention strategies. This literature review draws on a Two-Eyed Seeing approach and post-colonial theory to examine dominant Western approaches with an emphasis on Indigenous approaches. This literature review makes an important contribution to social work practice and policy by identifying key strengths and limitations of current dominant Western approaches as well as explore culturally safe and Indigenous approaches that can be used to decolonize and better inform the Indigenous youth suicide prevention work of social work clinicians and policy makers. Suicide Youth suicide Suicide behavior Suicide ideation Suicide intervention At risk Self-harm Self-mutilation Suicide prevention Self-injury Substance abuse Indigenous First Nations Metis Inuit Aboriginal Adolescent